Sozialer Sinn : Zeitschrift für hermeneutische Sozialforschung (De Gruyter Oldenbourg, 2000)
This journal is a forum for the discussion of hermeneutical social research. It brings together essays from the areas of the social and cultural sciences whose common focus is the hermeneutical interpretation and reconstructive explanation of the phenomena of social reality.